Work Analysis Of Work Stress And Nurse Productivity In Puskesmas Ngantru Tulungagung District - Yoga Satria , Benny; Peristiowati, Yuly; Nurdina (Universitas STRADA Indonesia, 2019)
The work productivity of nurses at the Puskesmas house plays an important role in deciding the organization's progress. high workload that can lead to work stress and interfere with work productivity. The purpose of this research is to know the relation of work load to work stress and productivity of nurses at Ngantru health center of Tulungagung regency. The design of this research is quantitative research using cross sectional approach with population of all nurses of Ngantru health center of Tulungagung regency number 31 people. The sample is all of the population with sampling technique in total sampling of 31 respondents. The data that have been collected is processed by ordinal regression statistic test. with significance α = 0.05. The results showed that 30 respondents, most of them had medium work load, 19 respondents (61.3%), most of them had moderate work stress, 16 respondents (51.6%) and almost half respondents have moderate work productivity, that is 15 respondents (48,4%). The result of regression analysis of ordinal between work load and work stress is known p-value = 0,000 (<0,05) which means reject H0 and accept H1 so that there is relation of work load to nurse work stress, between work stress with work productivity known p value -value = 0,000 (<0.05) which means reject H0 and receive H1 so that there is a workload relation to the productivity of the nurse. Efforts should be made to work and shift work effectively and efficiently to avoid workload and excessive work fluctuations resulting in the emergence of boredom and boredom that result in job stress.